Wura Bongi Monca dance as a promising context for fostering problem-solving skills in learning set theory - Khairullah; Rully Charitas Indra Prahmana; Nur Robiah Nofikusumawati Peni (Jurnal Elemen, 2025)
The Wura Bongi Monca dance embodies the philosophical values of Bima culture, which can be contextualized to facilitate students' understanding of abstract mathematical concepts, such as set theory. Although most ethnomathematics research has focused on concrete elements such as geometric shapes and numerical patterns in cultural practices, little attention has been given to how cultural values can support the teaching of abstract topics. Yet, local traditions hold significant potential to provide meaningful contexts for such learning. This study addresses that gap by investigating the traditional Bima dance Wura Bongi Monca as a contextual learning resource to introduce set theory and enhance students' problem-solving skills. Problem-solving is a key mathematical competency, indicating conceptual understanding, critical thinking, and the ability to apply knowledge in new situations. It also serves as a benchmark for evaluating the impact of culturally contextualized instruction. Using an ethnography approach including literature review, field observations, and interviews with cultural experts, the study interprets the symbolic meanings of Gerak Wura, the dance's core movements, and connects them to set theory concepts. The findings demonstrate that dance can foster conceptual understanding and cultural awareness, support culturally responsive mathematics education while preserving local heritage and providing insights for innovative instructional design.